Mapping the TYR gene reveals novel and previously reported variants in Eastern Indian patients highlighting preponderance of the same changes in multiple unrelated ethnicities. (2nd March 2020) - Ganguly, Kausik; Dutta, Tithi; Saha, Arpan; Sarkar, Devroop; Sil, Asim; Ray, Kunal; Sengupta, Mainak
Abstract: Oculocutaneous albinism (OCA) is a group of congenital autosomal recessive disorders with seven known subtypes (OCA1–OCA7) characterized by loss or absence of pigmentation in the skin, hair, and eyes. OCA1, caused by pathogenic variations in the tyrosinase ( TYR ) gene, has been documented to be the most prevalent subtype across the world including India. In the present study, we recruited 53 OCA‐affected individuals from 45 unrelated families belonging to 20 different marriage groups/ethnicities of 15 different districts of West Bengal. We took a targeted sequencing‐based approach to find the causal variations in the TYR gene. We report here identification of two novel potentially pathogenic variations [NM_000372.4:c.614C>T, NP_000363.1:p.(Pro205Leu), and NM_000372.4:c.1036+1=/G>T], one novel synonymous TYR variant [NM_000372.4:c.204=/A>G, NP_000363.1:p.(Gln68=)], two pathogenic variations documented for the first time in Indian OCA cases [NM_000372.4:c.1147G>A, NP_000363.1:p.(Asp383Asn), and NM_000372.4:c.585G>A, NP_000363.1:p.(Trp195*)], along with nine previously reported pathogenic variants in 36 out of 53 (∼68%) patients recruited. We report common haplotype backgrounds for the two most prevalent variations [NM_000372.4:c.124G>A, NM_000372.4:c.832C>T] in cases belonging to different marriage/ethnic groups, suggesting a possible founder effect. To our knowledge, this is the most comprehensive genetic study on OCA1 from India, firmly establishing OCA1 as the commonest form of albinism in this part of the world.